2017
DOI: 10.1016/j.cobeha.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The prefrontal cortex as a critical gate of negative affect and motivation in alcohol use disorder

Abstract: The prefrontal cortex (PFC) represents and executes the highest forms of goal-directed behavior, and has thereby attained a central neuroanatomical position in most pathophysiological conceptualizations of motivational disorders, including alcohol use disorder (AUD). Excessive, intermittent exposure to alcohol produces an allostatic dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis along with heightened forebrain glucocorticoid signaling that can damage PFC architecture and function. Negative affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…We chose to investigate phosphoprotein-level neuroadaptations in motivation-related brain regions including the prefrontal cortex, striatum, and dorsal hippocampus. Dysregulation of signaling within these areas has been implicated in the transition to drug addiction (Edwards & Koob, 2010; Egli, et al, 2012; Pahng et al, 2017). Corticostriatal circuitry is also intimately involved in affective self-regulation (Woo et al, 2015) and behavior selection (Baliki and Apkarian, 2015) in chronic pain states, while functional impairments due to chronic pain have been reported in the prefrontal cortex (Apkarian et al, 2004; Metz et al, 2009), striatum (Baliki et al, 2012), and hippocampus (Mutso et al, 2012; Vachon-Presseau et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We chose to investigate phosphoprotein-level neuroadaptations in motivation-related brain regions including the prefrontal cortex, striatum, and dorsal hippocampus. Dysregulation of signaling within these areas has been implicated in the transition to drug addiction (Edwards & Koob, 2010; Egli, et al, 2012; Pahng et al, 2017). Corticostriatal circuitry is also intimately involved in affective self-regulation (Woo et al, 2015) and behavior selection (Baliki and Apkarian, 2015) in chronic pain states, while functional impairments due to chronic pain have been reported in the prefrontal cortex (Apkarian et al, 2004; Metz et al, 2009), striatum (Baliki et al, 2012), and hippocampus (Mutso et al, 2012; Vachon-Presseau et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, these regions have included the amygdala, limbic and salience hub linked to emotional processing and response [24, 25], hippocampus, associated with learning and memory [26], insula, a major salience hub implicated in self-referential processing [20], and prefrontal cortex (PFC). The PFC is involved in executive functions [27] and includes sub-regions such as the orbitofrontal (OFC; implicated in emotional processing [28]) and anterior cingulate (ACC; associated with monitoring [29]) cortices. More recently, the involvement of reward- and motivation-related striatal regions [30], most commonly implicated in depression [31] and substance use [32], has also been explored [33•, 34].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that alcoholic individuals have lower PFC volume, activity and oxygenation, with consequent impairment in cognitive functions ( Asensio et al, 2016 , Pahng et al, 2017 , Schecklmann et al, 2007 , Wang et al, 2016 ). This condition has been associated to compulsive behavior and greater chance for relapse ( Volkow et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been widely shown to causes liver diseases and cancer ( Alcohol Consumption | Cancer Trends Progress Report, n.d. ). In the brain, deterioration of prosencephalic regions caused by alcohol abuse has been reported ( Asensio et al, 2016 , Pahng et al, 2017 ), with decreased oxygenation ( Schecklmann et al, 2007 ) and reductions of gray matter volume in the anterior cingulate and in the medial, orbitofrontal and prefrontal cortices ( Wang et al, 2016 ). Impairment in these structures has been accompanied by decreases in cognition ( Volkow, Koob, & McLellan, 2016 ) with lower control of impulsivity and emotional regulation, leading to inappropriate decision-making with further alcohol seeking behavior ( Goldstein & Volkow, 2011 ).…”
Section: Introductionmentioning
confidence: 99%